Bone marrow-derived mesenchymal stem cells promote colorectal cancer progression through paracrine neuregulin 1/HER3 signalling. Issue 4 (25th April 2012) - De Boeck, Astrid; Pauwels, Patrick; Hensen, Karen; Rummens, Jean-Luc; Westbroek, Wendy; Hendrix, An; Maynard, Dawn; Denys, Hannelore; Lambein, Kathleen; Braems, Geert; Gespach, Christian; Bracke, Marc; et al.
Abstract : Objective: Bone marrow-derived mesenchymal stem cells (BM-MSC) migrate to primary tumours and drive tumour progression. This study aimed to identify the molecular mechanisms associated with these heterotypic cellular interactions and analyse their relevance in colorectal cancer (CRC). Design: Paracrine interactions of BM-MSC with CRC cells were studied using collagen invasion assays, cell counts, flow cytometric cell-cycle analysis and tumour xenograft models. The role of neuregulin 1 (NRG1) and the human epidermal growth factor receptor (HER) family pathways were investigated using tyrosine kinase assays, mass spectrometry, pharmacological inhibition, antibody-mediated neutralisation and RNA interference. Transmembrane neuregulin 1 (tNRG1), HER2 and HER3 expression was analysed in primary CRC (n=54), adjacent normal colorectal tissues (n=4), liver metastases (n=3) and adjacent normal liver tissues (n=3) by immunohistochemistry. Results: BM-MSC stimulate invasion, survival and tumorigenesis of CRC through the release of soluble NRG1, activating the HER2/HER3-dependent PI3K/AKT signalling cascade in CRC cells. Similarly, tumour-associated mesenchymal cells (T-MC) in CRC demonstrate high tNRG1 expression, which is significantly associated with advanced Union for International Cancer Control stage (p=0.005) and invasion depth (p=0.04) and decreased 5-year progression-free survival (p=0.01). HER2 and HER3 show membrane localisation in cancer cells of CRC tissue. Conclusion: Paracrine NRG1/HER3 signals initiated by BM-MSC and T-MC promote CRC cell progression, and high tNRG1 expression is associated with poor prognosis in CRC.